1963
DOI: 10.19182/remvt.7206
|View full text |Cite
|
Sign up to set email alerts
|

Note complémentaire sur un essai de lutte contre <em>Glossina fuscipes fuscipes</em> en République Centrafricaine

Abstract: cf. fichier PDF de l'article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1974
1974
1974
1974

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Selective application of insecticide to these sites was considered to have eradicated this species from a 35-mile 2 area (Chadwick et al, 1964). Finelle (1967) selectively applied insecticide to the resting sites of G. f. fuscipes in the Republique Centrafricaine. Challier (1968), in Haute Volta, showed that G. p. gambiensis Vanderplank at night rested particularly on leaves of small plants, confirming studies by McDonald (1960) on G. p. palpalis in Nigeria.…”
Section: Breeding Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Selective application of insecticide to these sites was considered to have eradicated this species from a 35-mile 2 area (Chadwick et al, 1964). Finelle (1967) selectively applied insecticide to the resting sites of G. f. fuscipes in the Republique Centrafricaine. Challier (1968), in Haute Volta, showed that G. p. gambiensis Vanderplank at night rested particularly on leaves of small plants, confirming studies by McDonald (1960) on G. p. palpalis in Nigeria.…”
Section: Breeding Sitesmentioning
confidence: 99%
“…The insecticide used during the work in the far north of Nigeria was DDT wettable powder, generally applied as a suspension of 2\% active ingredient. Where the dry season is shorter and less harsh it has been common practice to apply either DDT or dieldrin as an emulsion concentrate; dieldrin has been particularly widely used in recent years (e.g., Wooff, 1965;Finelle, 1967;Robertson & Kluge, 1968;Robertson et al, 1972).…”
Section: Application Of Insecticides From the Groundmentioning
confidence: 99%